Soft magnetic material and method for manufacturing the same
Patent Information
- Application Number
- JP2025029916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2026-09-08
Smart Images

Figure 2026142748000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a soft magnetic material and the like. [Background Art]
[0002] A soft magnetic material (member) is essential for forming a magnetic circuit. A soft magnetic material is usually made of an iron base material having high magnetic permeability and high saturation magnetization. For soft magnetic materials used in alternating magnetic fields, silicon steel (particularly smelted material) capable of suppressing iron loss (eddy current loss, hysteresis loss, etc.) is often used. A soft magnetic material made of high-silicon steel containing a large amount of Si (a ferrite stabilizing element) is expected to reduce iron loss and the like.
[0003] However, high-silicon steel has low toughness and is difficult to form. For this reason, common soft magnetic materials are made of silicon steel containing about 1 to 3 wt% of Si.
[0004] Under such circumstances, it has been proposed to form a soft magnetic material made of high-silicon steel by additive processing using a so-called metal 3D printer or the like. Descriptions related to this can be found, for example, in the following documents. [Prior Art Documents] [Non-Patent Documents]
[0005] [Non-Patent Document 1] A. Andreiev, K. Hoyer, F. Hengsbach, M. Haase, L. Tasche, K. Duschik, M. Schaper; Powder bed fusion of soft-magnetic iron-based alloys with high silicon content, Journal of Materials Processing Technology, vol. 317, (2023), 117991 [Non-Patent Document 2] JY Hwang, HY Jung; Investigation of Cracking Behavior of Fe-6.7 Wt Pct Si Manufactured Using Laser Powder Bed Fusion, Metall. Mater. Trans. A 54, 3752-3766 (2023). [Overview of the project] [Problems that the invention aims to solve]
[0006] Non-patent document 1 describes a method of suppressing cracking of fabricated objects (soft magnetic materials) made of high-silicon steel by heating the base plate to 700°C during fabrication using laser powder bed fusion (L-PBF) to reduce distortion caused by thermal shock and thermal shrinkage. However, this method does not allow for energy saving and fabrication can only be performed near the base plate where temperature control is possible.
[0007] Non-patent document 2 describes how, during L-PBF fabrication, increasing the scanning speed and cooling speed reduces the generation of a hard phase that causes cracking, thereby suppressing cracking of fabricated objects made of high-silicon steel. However, such methods are highly dependent on the equipment and have limited design flexibility.
[0008] This invention has been made in view of these circumstances, and aims to provide a new soft magnetic material made of high-silicon steel. [Means for solving the problem]
[0009] Through diligent research, the inventor conceived of a soft magnetic material made of high-silicon steel with specific ceramic particles dispersed in it, and successfully realized this concept. By further developing this result, the inventor completed the present invention described below.
[0010] 《Soft magnetic material》 The present invention relates to a soft magnetic material comprising ceramic particles dispersed in an iron substrate, wherein the iron substrate is made of high-silicon steel containing 5 to 8 mass% of Si relative to the entire iron substrate, and the ceramic particles contain a compound of Ti and / or Zr with one or more of C, N, or O, wherein the compound is present in a soft magnetic material in an amount of 0.3 to 3 volume% relative to the entire iron substrate.
[0011] The soft magnetic material of the present invention, made of high-silicon steel, not only exhibits high magnetic properties, low loss, and high strength, but is also resistant to cracking. This is thought to be because certain ceramic particles act as crystallization or precipitation nuclei for ferrite (body-centered cubic lattice / BCC), resulting in refinement or equiaxation of the metallic structure (crystal grains) of the high-silicon steel.
[0012] 《Manufacturing method》 The present invention can also be understood as a method for manufacturing soft magnetic materials. For example, the present invention may be a manufacturing method that obtains the above-mentioned soft magnetic material by irradiating a raw material powder with a high-energy beam to melt and solidify it. This manufacturing method is carried out by additive processing such as directed energy deposition (DED) or powder bed fusion (PBF). Such additive processing can also increase the degree of freedom in the shape of the soft magnetic material.
[0013] 《Modeling powder》 The present invention may be understood as a raw material powder used in the above-described manufacturing method (powder molding). This raw material powder may, as a whole, contain specific ceramic particles, a predetermined amount of Si, and Fe as the main remainder. The raw material powder may be a mixed powder obtained by mixing multiple types of powders, or it may be a complete alloy powder consisting of particles prepared to the desired overall composition.
[0014] "others" Unless otherwise specified, "x to y" as used herein includes the lower limit x and the upper limit y. A range such as "a to b" may be newly established with any numerical value included in the various numerical values or numerical ranges described herein as a new lower limit or upper limit. In addition, "x to y μm" as used herein means x μm to y μm. The same applies to other unit systems. [BRIEF DESCRIPTION OF DRAWINGS]
[0015] [Figure 1A] These are an SEM image and an IPF map of Sample 11. [Figure 1B] This is an elemental mapping image of Sample 11 obtained by EDS. [Figure 2A] These are SEM images and IPF maps of Samples 21 to 23. [Figure 2B] These are elemental mapping images of Sample 21 and Sample 23. [Figure 2C] This is an IPF map of Sample 211. [Figure 3] These are SEM images of Sample C11 and Sample C21. [Figure 4] These are IPF maps of Sample C12 and Sample C21. [Figure 5] This is a schematic diagram illustrating the "Baker-Nutting orientation relationship" between ferrite and ceramic particles. [MODE FOR CARRYING OUT THE INVENTION]
[0016] One or more constituent elements arbitrarily selected from the present specification may be added to the constituent elements of the present invention. The contents described in the present specification appropriately apply not only to the soft magnetic material but also to a manufacturing method (additive manufacturing method), powder for modeling, and the like. Note that even method-based constituent elements can serve as constituent elements relating to an article.
[0017] <<Soft Magnetic Material>> The soft magnetic material consists of an iron base material (high silicon steel) containing ceramic particles. The details are as follows.
[0018] (1) Iron base material The iron base material that forms the matrix (base material) of the soft magnetic material is preferably made of high-silicon steel containing, for example, 5-8 mass%, 5.5-7.5 mass%, or 6-7 mass% of Si relative to the total. If Si is too high, the impact resistance and magnetic properties of the soft magnetic material may decrease. If Si is too low, the electrical resistivity (specific resistivity) of the soft magnetic material cannot be sufficiently increased. In this specification, "silicon steel" means an iron alloy containing Si, and the presence or absence of C is irrelevant. Furthermore, if we were to specify, the Fe, which is the main remainder of the iron base material, is preferably contained in, for example, 85-95 mass%, 88-94 mass%, or 92-93 mass% relative to the total. The remainder may also contain unavoidable impurities.
[0019] The iron substrate (high-silicon steel) may contain ferrite-stabilizing elements other than Si. These ferrite-stabilizing elements may include one or more of the following: Al, Cr, Nb, V, W, Mo, etc.
[0020] For example, Al may be present in amounts of 0.3 to 3% by mass, 0.5 to 2.5% by mass, or 1 to 2% by mass relative to the entire iron substrate. Like Si, Al can increase the electrical resistivity (resistivity) of soft magnetic materials.
[0021] Elements such as Cr, Nb, V, W, and Mo may be present in total amounts of 0.1 to 1 mass%, 0.2 to 0.7 mass%, or 0.3 to 0.5 mass% relative to the entire iron substrate. Although these elements are also ferrite-stabilizing elements, they can increase the coercivity of soft magnetic materials by solid dissolving in the iron substrate (high-silicon steel), so it is preferable to have them in small amounts.
[0022] In this specification, chemical composition (component composition) refers to the mass ratio relative to the entire substance (100% by mass), unless otherwise specified, and is indicated as "%" or numerically only as appropriate. This composition is identified by analyzing the componentally stable region using methods such as energy dispersive X-ray spectroscopy (EDS) or electron probe microanalyzer (EPMA).
[0023] (2) Ceramic particles Ceramic particles are dispersed particles in an iron substrate (matrix). The ceramic particles may be supplied as part of the raw material powder, or they may crystallize or precipitate.
[0024] Examples of ceramic particles that refine the metallic structure (ferrite crystal grains) of iron substrates include carbides, nitrides, or oxides of Ti and / or Zr. These also include composite compounds such as carbonitrides and oxynitrides.
[0025] Such compounds (ceramic particles) are present in amounts of, for example, 0.3-3% by volume, 0.5-2% by volume, or 0.8-1.5% by volume relative to the entire iron substrate. Too little of the compound will have little effect, while too much may degrade the magnetic properties of the soft magnetic material.
[0026] The size (referred to as "particle size" regardless of shape) of ceramic particles dispersed in an iron substrate is, for example, 0.1 to 20 μm, 0.5 to 10 μm, or 0.7 to 5 μm. The particle size can be determined, for example, by image analysis of a metal microstructure (e.g., a scanning electron microscope image) and taking the arithmetic mean of the longest ceramic particles within the field of view.
[0027] Ceramic particles are more likely to preferentially become nuclei for ferrite (BCC) crystallization if they satisfy the Baker-Nutting relationship shown in Figure 5 (referred to as the "BN relationship" / References: ZG Yang, M. Enomoto; Discrete lattice plane analysis of baker-nutting related B1 compound / ferrite interfacial energy, Mater. Sci. Eng. A, 332 (2002), pp. 184-192; Keiichiro Kawanishi et al., "Ferrite transformation behavior at the steel / B1 compound interface", Iron and Steel, Vol.96, No.3 (2010), pp.23-28, etc.). Specifically, the BN relationship is as follows: (i) The (001) plane of the ceramic particle is parallel to the (001) plane of the ferrite. (ii) The
[0100] direction of the ceramics is parallel to the
[0110] direction of the ferrite. (iii) The lattice constant of the ceramic particles is approximately (√2 = 1.4) times that of the lattice constant of ferrite.
[0028] The crystal structure is determined by relations (i) and (ii) which define the spatial relative positions between crystals. Furthermore, the elements (component composition) that make up the ceramic particles (compounds) are determined by relation (iii) which defines the lattice constant (a).
[0029] Examples of ceramic particles that satisfy this BN relationship include titanium-based ceramic particles and zirconium-based ceramic particles with a crystal structure of the NaCl type. Specifically, these are compounds such as TiC, TiN, TiO, ZrC, ZrN, ZrO, and composites thereof (carbonitrides, oxynitrides, etc.). Ceramic particles may consist only of these compounds (individual or composite), or they may consist of, for example, 80% or more of these compounds and the remainder (less than 20% by volume) of a compound (with an NaCl-type crystal structure) consisting of one or more of the following: VC, VN, NbC, NbN, TaC, TaN, CrC, CrN, etc.
[0030] For reference, the lattice constants of each material are as follows: ferrite: 2.87 Å, TiC: 4.32 Å, TiN: 4.24 Å, ZrC: 4.70 Å, and ZrN: 4.58 Å. The lattice constants of each ceramic particle are approximately 1.4 to 1.6 times that of ferrite.
[0031] 《Manufacturing method》 Soft magnetic materials can be manufactured by various methods, but for example, they can be obtained by powder (additive) fusion. The details are as follows.
[0032] (1) Raw material powder / modeling powder The raw material powder is not limited by its production process, particle morphology (shape, size, etc.) or the like. The raw material powder may be atomized powder or pulverized powder. As a whole, the raw material powder may be a (complete) alloy powder smelted to have a desired composition or a mixed powder blended to have a desired composition, as long as it satisfies the components and formulations of the above-described iron base material and ceramic particles.
[0033] The raw material powder is preferably used with a particle size suitable for the specifications of the soft magnetic material and the modeling method. The particle size is, for example, approximately 0.1 to 100 μm, 1 to 50 μm, or 5 to 25 μm. The ceramic powder (which may be two or more types of powder) in the mixed powder is finer than the iron base material powder, and for example, may have a particle size of 0.1 to 120 μm or 1 to 10 μm. Conversely, the iron base material powder (which may be two or more types of powder) may have a particle size of 5 to 100 μm or 10 to 50 μm.
[0034] In this specification, unless otherwise specified, the particle diameter (regardless of particle shape) is specified by the maximum length of the particle, and the particle size is specified by the powder sieving method (see: JIS Z 8801, Z 8815, etc.). For example, particle size: y to x (y < x / μm) means a powder composed of particles that do not pass through a sieve with an opening of y (μm) and pass through a sieve with an opening of x (μm). The particle size identification may be substituted or complemented as appropriate by using a laser diffraction / scattering method (JIS Z 8825, etc.), dynamic light scattering method, or the like.
[0035] (2) Irradiation step A high-energy beam is irradiated onto the raw material powder prepared or blended to have a desired component composition, and a soft magnetic material is obtained as a shaped article obtained by melting and solidifying the raw material powder.
[0036] High-energy beams are, for example, lasers or electron beams with high energy density (fluence). Lasers are selected and adjusted as appropriate in terms of type (amplification medium, excitation source, optical resonator, etc.), output, energy density, irradiation area, overlap rate, etc. Lasers can be continuous-wave lasers or pulsed lasers. One example of a laser is a fiber laser (a type of solid-state laser) that uses an optical fiber (for example, a double-clad fiber doped with rare earth elements in the core) as the amplification medium. The irradiation process may be performed using a powder bed fusion apparatus (PBF) or a directed energy deposition apparatus (DED), etc.
[0037] Depending on the beam irradiation range and trajectory, the desired shape (area) is formed. By repeating the irradiation process (including the supply of raw material powder), a three-dimensional additively fabricated object (soft magnetic material) can also be obtained.
[0038] (3) Heat treatment The fabricated object may be subjected to heat treatment after the irradiation process.
[0039] After melting and solidifying, the fabricated object has a metallic structure in which the ferrite crystal grains have been refined and even isotropic (equaxed). An excessive increase in the size of the crystal grains leads to an increase in the coercivity and a decrease in the permeability of the soft magnetic material. Therefore, the fabricated object may be heated to adjust the size of the ferrite crystal grains (grain adjustment process). This heat treatment is performed, for example, in an inert atmosphere (noble gas atmosphere, nitrogen gas atmosphere, vacuum atmosphere, etc.) at 1000-1400°C or 1200-1350°C for 0.5-8 hours or 1-4 hours.
[0040] When the crystal grain size of the ferrite constituting the fabricated object is adjusted to, for example, 10-200 μm, 30-150 μm, or 50-100 μm, the properties of the soft magnetic material (low coercivity, high permeability, etc.) can be improved.
[0041] The grain size of ferrite can also be determined, for example, by analyzing an image of the microstructure and taking the arithmetic mean of the longest grains within the field of view. This image may include electron microscope images (SEM images, etc.) or inverse pole figure orientation maps (IPF maps) obtained by electron backscatter diffraction (EBSD).
[0042] In addition to the grain adjustment process, other heat treatments (for example, 1 to 8 hours at 800 to 1000°C) may be performed after molding to reduce thermal distortion that occurs during solidification.
[0043] 《Soft magnetic material》 Soft magnetic materials are not limited by their application or form (shape, size, etc.). They may be three-dimensional components or two-dimensional layers or films (including thin films). Typical examples of soft magnetic materials are yokes and cores. [Examples]
[0044] A soft magnetic material (sample) made of silicon steel (iron base material) was fabricated by powder bed fusion, and its metallic structure (crystal grains) was evaluated. The present invention will be described in more detail based on this specific example.
[0045] Sample preparation (1) Raw material powder As iron-based powders, Fe-3Si powder (particle size: 45-105 μm) and Fe-6.5Si powder (particle size: 45-105 μm) were prepared. These silicon steel powders are commercially available molding powders (manufactured by Sanyo Special Steel Co., Ltd.). The chemical composition of each powder is shown as a mass percentage of the total iron-based powder, and where appropriate, the amount of alloying elements (mass%) is shown numerically only (remainder: Fe).
[0046] As ceramic powders, we prepared TiN powder (particle size: 0.7-1.9 μm) and TiC powder (particle size: 1-2 μm). These ceramic powders are commercially available test powders (manufactured by Nippon Shinkinzoku Co., Ltd.).
[0047] Silicon steel powder and ceramic powder were weighed and mixed powders were prepared as shown in Tables 1 and 2. The amount of ceramic powder is expressed as a volume ratio to the total mixed powder (iron base powder + ceramic powder), and the amount (vol%) is shown numerically only where appropriate. The volume of each powder was determined from its true density and mixed weight. The silicon steel and ceramic powders were rotary mixed (45 rpm x 1 hour) using a pot mill manufactured by Nidek Drive Technology Co., Ltd.
[0048] (2) Powder modeling (irradiation process) Powder bed fusion (PBF) fabrication was performed using directed energy deposition (DED) and powder bed fusion (PBF). A laser processing tester manufactured by Enshu Co., Ltd. was used for DED, and a 2Create machine manufactured by 2oneLab was used for PBF. In both cases, a laser (high-energy beam) was used as the heat source, and the irradiation conditions for each sample are shown in Tables 1 and 2. Fabrication was performed in an inert atmosphere (Ar gas stream), and the number of layers was adjusted for each sample.
[0049] (3) Heat treatment (grain adjustment process) The fabricated object of sample 21 was further heated in a vacuum atmosphere at 1300°C for 2 hours. This heat-treated object is referred to as sample 211.
[0050] Observation and Analysis The metallic structure of each sample was observed using a scanning electron microscope (SEM). Furthermore, the distribution of constituent elements in the metallic structure (elemental mapping image) was obtained using an energy-dispersive X-ray spectrometer (EDS) attached to the SEM. The distribution of Ti shown in the elemental mapping images (Figures 1B and 2B) reveals the dispersion state of the ceramic particles. Note that light elements (N and C) are difficult to detect with EDS, so their elemental mapping images were omitted where appropriate.
[0051] Furthermore, the metal structure was analyzed using an electron beam backscatter diffraction (EBSD: MSC-2200, TSL Solutions Co., Ltd.) to create an inverse pole figure orientation map (IPF map). The results obtained are shown in Figures 1A, 1B (collectively referred to as "Figure 1"), 2A, 2B, 2C (collectively referred to as "Figure 2"), 3, and 4.
[0052] "evaluation" As can be seen from Figures 1 and 2, even with fabricated objects made of high-silicon steel with a Si content of 6% or more, if ceramic particles were dispersed in the iron substrate, no cracks were observed in the metal structure (sample 11, samples 21-23), regardless of the fabrication method (DED, PBF).
[0053] It was confirmed that all of these metal structures consisted of fine, equiaxial crystal grains (ferrite). As is evident from the IPF maps of sample 21 (Figure 2A) and sample 211 (Figure 2C), the crystal grain size of the ferrite could be adjusted by post-fabrication heat treatment. This confirmed that the magnetic properties of the fabricated soft magnetic material could be controlled according to the required specifications.
[0054] On the other hand, as can be seen from Figure 3, the metallic structure of fabricated objects made of high-silicon steel without ceramic particles (samples C11 and C21) showed numerous cracks regardless of the fabrication method (DED and PBF).
[0055] For fabricated objects made of silicon steel with a Si content of approximately 3%, no cracks were observed in the metallic structure (samples C12 and C21), even without the inclusion of ceramic particles. However, as can be seen in Figure 4, these metallic structures were composed of coarse ferrite that grew in one direction.
[0056] Thus, it has been confirmed that the present invention can provide a soft magnetic material made of high-silicon steel while suppressing the occurrence of defects (such as cracks).
[0057] [Table 1]
[0058] Table 2
Claims
1. A soft magnetic material in which ceramic particles are dispersed in an iron substrate, The iron base material is made of high-silicon steel containing 5 to 8% by mass of Si relative to the entire iron base material. The ceramic particles contain a compound of Ti and / or Zr with one or more of C, N, or O. The compound is a soft magnetic material present in an amount of 0.3 to 3 volume percent relative to the entire iron substrate.
2. The compound is a soft magnetic material according to claim 1, wherein the crystalline structure is of the NaCl type.
3. The soft magnetic material according to claim 1, wherein the iron substrate contains, in total, 0.1 to 1% by mass of one or more of Cr, Nb, V, W, or Mo and / or 0.3 to 3% by mass of Al, relative to the entire iron substrate.
4. The soft magnetic material is a laminated product as described in claim 1.
5. The system includes an irradiation process to obtain a fabricated object by irradiating a raw material powder with a high-energy beam to melt and solidify it. A method for producing a soft magnetic material according to any one of claims 1 to 4.
6. The method for manufacturing a soft magnetic material according to claim 5, further comprising a grain adjustment step of heating the molded material to adjust the size of the ferrite crystal grains.
7. The method for producing a soft magnetic material according to claim 5, wherein the raw material powder is a mixed powder or a complete alloy powder.
8. A method for producing a soft magnetic material according to claim 5, which is carried out by directed energy deposition or powder bed fusion bonding.